Mental preparation for nationality-based challenges at the Paris 2024 Olympic Games: a multi-level intervention - Gutman, T.; Cohen, D.; Tzafrir, A.; Epstein, M.; Meretyk, N.; Benedik, B.; Galily, Y. (International Journal of Sport and Exercise Psychology, 2026)
The Olympic Games are widely recognised as a major emotional challenge for athletes and support staff. For the Israeli delegation, the Paris 2024 Games brought an additional layer of psychological complexity. Amid the backdrop of the ongoing Middle East conflict, which intensified following the October 7 tragic events, Israeli athletes encountered several nationality-based challenging events throughout the Olympic year, including verbal hostility, protests, and symbolic gestures. While such events were expected to be limited during the Paris Games, sport psychology practitioners working with the national teams chose to develop a focused intervention to help the delegation remain performance oriented. The rationale was to address these potential challenges thoughtfully, without overemphasising their significance. The intervention was grounded in an OSP and CBS, aiming to equip athletes and staff with tools to manage external pressures while embodying the Olympic spirit in the face of adversity. This paper outlines the theoretical foundations, practical implementation, and post-Games reflections that were collected from both the practitioners and the intervention leaders, who were also members of the delegation team.